THE INFLUENCE OF ADAPTIVE, COMPETENCE, AND TRANSFORMATIVE LEADERSHIP ON INDIVIDUAL PERFORMANCE - Sigit Kurnianto; Sri Ningsih (EKUITAS (Jurnal Ekonomi dan Keuangan), 2024)
This study aims to investigate the influence of adaptive, competence, and transformative leadership on individual performance. This quantitative study uses Partial Least Square Structural Equation Modeling (PLS-SEM) to test the hypothesis. This paper uses the survey method, and data was collected using questionnaires. As many as 271 East Java, Indonesia civil servants participated in this study. The results showed that adaptive, competent, and transformative leadership positively affects individual performance. This research can provide insight for government officials to improve ASN performance by paying attention to Adaptive ability and competence. In addition, it helps ASN structural officials develop effective leadership strategies to improve individual performance with transformative leadership. This research has the potential to help increase the effectiveness and productivity of ASN, which in turn will positively impact public services and state development. Previous research that relates to individual performance still needs to be made available. In addition, this research is the only study that applies transformative, adaptive, and competency leadership to individual performance in Indonesia, especially ASN in East Java.